Neural segregation in left inferior frontal gyrus of semantic processes at different levels of syntactic hierarchy. (4th July 2022) - Li, Xun; Jiang, Xiaoming; Chang, Wenshuo; Tan, Yingying; Zhou, Xiaolin
Abstract: Humans are unique in their ability to parse hierarchical structures of sentences. Previous studies demonstrated that syntactic processes at different hierarchies are subserved by distinct subregions in left inferior frontal gyrus (LIFG), in which BA45 is mainly involved in processing lower-level syntactic structures and BA44 is mainly involved in processing higher-level syntactic structures. However, little is known about whether semantic processes at different syntactic hierarchies show similar dissociations in LIFG. In the present fMRI experiment, participants read sentences with the structure "subject noun + verb + numeral + classifier + object noun", in which the object noun is constrained by the classifier at the lower-level and by the verb at the higher-level. The object noun was manipulated to be either semantically congruent or incongruent with the classifier at the lower-level and/or with the verb at the higher-level. Both the whole brain contrasts and the region of interest (ROI) analyses showed that, in LIFG, the semantic process of integrating the object noun with the classifier induced stronger activation in BA45 whereas the semantic process of integrating the object noun with the verb induced stronger activation in BA44. This dissociation demonstrates a neural segregation for semantic processes at different syntactic hierarchies, with the lower-level process relying more on neural substrates for general semantic processes and the higher-level process relying more on neural substrates for processing structural hierarchies. Highlights: In a minimal task demand, activations in LIFG enhanced for semantic congruence vs. incongruence. The BA45 for the lower-level semantic process peaked around the locus related to semantic unification. The BA44 for the higher-level semantic process peaked around the locus related to syntactic unification.